Metabolomic Aspects of Conservative and Resistance-Related Elements of Response to Fusarium culmorum in the Grass Family - Anna Piasecka; Aneta Sawikowska; Natalia Witaszak; Agnieszka Waśkiewicz; Marta Kańczurzewska; Joanna Kaczmarek; Justyna Lalak-Kańczugowska (Cells, 2022)
Background: Fusarium head blight (FHB) is a serious fungal disease affecting crop plants, causing substantial yield reductions and the production of mycotoxins in the infected grains. Achieving progress in the breeding of crops with increased resistance and maintaining a high yield is not possible without a thorough examination of the molecular basis of plant immunity responses. Methods: LC-MS-based metabolomics approaches powered by three-way ANOVA and the selec-tion of differentially accumulated metabolites (DAMs) were used for studying plant immunity. A correlation network and functional enrichment analysis were conducted on grains of barley and wheat genotypes that were resistant or susceptible to FHB, as well as on the model grass Brachypodium distachyon (Bd), as this is still poorly understood at the metabolomic level. Results: We selected common and genotype-specific DAMs in response to F. culmorum inoculation. The immunological reaction at the metabolomic level was strongly diversified between resistant and susceptible genotypes. DAMs that were common to all tested species from the porphyrin, flavonoid, and phenylpropanoid metabolic pathways were highly correlated, reflecting con-servativeness in the FHB response in the Poaceae family. Resistance-related DAMs belonged to different structural classes, including tryptophan-derived metabolites, pyrimidines, the amino acids proline and serine, as well as phenylpropanoids and flavonoids. The physiological re-sponse to F. culmorum of Bd was close to that of barley and wheat genotypes; however, metabo-lomic changes were strongly diversified. Conclusions: Combined targeted and untargeted metabolomics provides comprehensive knowledge about significant elements of plant immuni-ty that have the potential to be molecular biomarkers of enhanced resistance to FHB in the grass family. Thorough examination of the Bd metabolome in juxtaposition with diversified geno-types of barley and wheat facilitated its use as a model grass for plant–microbe interaction.